FLYPAPER EFFECT PADA PENDAPATAN ASLI DAERAH (PAD), DAN DANA ALOKASI UMUM (DAU) TERHADAP BELANJA PEMERINTAH DAERAH KABUPATEN NGANJUK PERIODE 2012-2016 - Susanti Eka Wahyuni; Indrian Supheni (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims to find out about Local Revenue (PAD) and General Allocation Fund (DAU) either partially or simultaneously to the Local Government Expenditures Nganjuk District 2009-2013 period and what happened Flypaper Effect.This research is a quantitative research. In this study data from the Office of Revenue Management of Finance and Regional Assets Nganjuk District of Local Revenue (PAD), General Allocation Fund (DAU) and Regional Expenditure period 2012-2016. This data is secondary data that is realization data of Revenue and Expenditure Budget Year 2009-2013 specially on Original Revenue, General Allocation Fund and Expenditure Area. This data is then tested by classical principle test, while data analysis using descriptive statistical analysis and multiple linear regression.The results of this study indicate: 1) Local Original Income (PAD) is not significant to the Regional Expenditure which is the result of. 2) General Allocation Fund has a positive and significant impact on Regional Expenditure. It is a result of. With a positive regression level obtained by 1.857. 3) Local Revenue and General Allocation Fund directly regarding Regional Expenditure on Nganjuk District Period 2012-2016. This is evidenced from the value of F hitung 70.353 with a significance of 0.014. Visible this significance is smaller than 0.05. 4) Flypaper Effect on Local Government Expenditure Nganjuk Regency Period 2012-2016. Which is the response of the Local Government of Nganjuk Regency to the General Allocation Fund is greater than the Local Original Income in financing all expenditures.Â Keywords: Local Revenue, General Allocation Fund, Regional Expenditure, and Flypaper Effect.